Ionic Liquids: Lubrication Mechanism of Phosphonium Phosphate Ionic Liquid in Nanoscale Single‐Asperity Sliding Contacts (Adv. Mater. Interfaces 17/2020). Issue 17 (11th September 2020) - Li, Zixuan; Dolocan, Andrei; Morales‐Collazo, Oscar; Sadowski, Jerzy T.; Celio, Hugo; Chrostowski, Robert; Brennecke, Joan F.; Mangolini, Filippo
Abstract : Ionic liquids (ILs) are promising chemical compounds for lubricating moving mechanical components. In article number 2000426 by Filippo Mangolini and coworkers, an understanding of the mechanism by which ILs containing alkyl phosphonium cations and alkyl phosphate anions reduce friction is established at the nanoscale by combining in situ atomic force microscopy and ex situ laterally‐resolved surface spectroscopic measurements.